Clotrimazole–cyclodextrin based approach for the management and treatment of Candidiasis – A formulation and chemistry-based evaluation. (3rd July 2016) - Mohammed, Noorullah Naqvi; Pandey, Pankaj; Khan, Nayaab S.; Elokely, Khaled M.; Liu, Haining; Doerksen, Robert J.; Repka, Michael A.
Abstract : Clotrimazole (CT) is a poorly soluble antifungal drug that is most commonly employed as a topical treatment in the management of vaginal candidiasis. The present work focuses on a formulation approach to enhance the solubility of CT using cyclodextrin (CD) complexation. A CT–CD complex was prepared by a co-precipitation method. Various characterization techniques such as differential scanning calorimetry, infrared (IR) and X-ray spectroscopy, scanning electron microscopy and nuclear magnetic resonance (NMR) spectroscopy were performed to evaluate the complex formation and to understand the interactions between CT and CD. Computational molecular modeling was performed using the Schrödinger suite and Gaussian 09 program to understand structural conformations of the complex. The phase solubility curve followed an A L -type curve, indicating formation of a 1:1 complex. Molecular docking studies supported the data obtained through NMR and IR studies. Enthalpy changes confirmed that complexation was an exothermic and enthalpically favorable phenomenon. The CT–CD complexes were formulated in a gel and evaluated for release and antifungal activity. The in vitro release studies performed using gels demonstrated a sustained release of CT from the CT–CD complex with the complex exhibiting improved release relative to the un-complexed CT. Complexed CT–CD exhibited better fungistatic activity toward different Candida species than un-complexed CT.